2022
DOI: 10.3390/logistics6010021
|View full text |Cite
|
Sign up to set email alerts
|

Integration of Blockchain Technology and Prioritization of Deployment Barriers in the Blood Supply Chain

Abstract: Background: This research aims to prioritize the blood supply hub for coping barriers of implementation blockchain (BC) in supply chain management (SCM). Nowadays, blood supply is a crucial matter that plays an essential role in people’s lives. Hence, tracing the supply of blood is very substantial. One of the ways for the SCM of blood supply is a blockchain system. It shows how all traces of the SCM stream can flow from raw material to receiving blood into end users. However, there are many barriers to the im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…In the literature, some scholars investigated medical and pharmaceutical waste recycling networks as supply chain network design and construction problems. The supply chain management helps companies to reduce operating costs, speed up processes, and ultimately increase customer satisfaction [13]. A number of these studies are presented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In the literature, some scholars investigated medical and pharmaceutical waste recycling networks as supply chain network design and construction problems. The supply chain management helps companies to reduce operating costs, speed up processes, and ultimately increase customer satisfaction [13]. A number of these studies are presented.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The results showed that business owners' unwillingness was the highest priority among the nine obstacles. Additionally, blockchain implementation for blood and drug supply chain management requires more payment [18]. [23].…”
Section: Literature Reviewmentioning
confidence: 99%
“…The use of a blockchain is proposed to ensure the integrity of the data. Another proposition for the use of blockchains to trace the blood supply as part of supply chain management for blood supply hubs is made in [48].…”
Section: Introductionmentioning
confidence: 99%